PENINGKATAN PRODUKTIVITAS MENGGUNAKAN METODE LINE BALANCING PADA PROSES PENGEMASAN DI PT.XYZ - Ismail Fardiansyah; Tri Widodo (Journal Industrial Manufacturing, 2018)
PT.XYZ is a logistic service provider company. One of their division is a contract logistic. Contract logistic is division that maintain the warehouse of customer. One of Operation in warehouse is value added service (VAS) that additional services based on customer requirement one of VAS process in PT.XYZ is a packaging process. In order to meet the customer requirement, PT.XYZ should be productive and efficient in Operation. It can be happen through by line balancing. This paper explains about line balancing implementation in VAS process at PT.XYZ to increase productivity. Line balancing analysis in VAS process for current condition among others total cycle time are 131 second by 10 operator, it’s impact to productivity by 106 box/operator/day, and line efficiency by 94%. Based on this fact, improvement conducted through balancing workload and waste reduction to get optimum condition. The result of improvement are increase productivity by 104%, increase line efficiency by 3%, and cycle time reduction by 15%. PT.XYZ need to continue conduct waste elimination and regular monitor of line balancing analysis to achieve sustainability of optimum productivity.